Studi Kelayakan Pendirian Pusat Pembelajaran Piano untuk Penderita Autisme di Surabaya - Marselina Rusli; Prayonne Adi (Jurnal Titra, 2020)
Piano learning center for autism is a learning center with music therapy and piano concept. Learning center is founded to answer autistic needed in focus, auditory, and emotion. To make a right foundation, feasibility study need to analysis from 3 segment are, market segment, technical segment, and financial segement. Market segment for this learning center examine competitor, SWOT analysis, focus, auditory, emotion autismetic, interest for learning center, potential market and business model canvas. Techinical segment examine license for operation and enstablised, worker, facility and layout design, room needs, and teaching schedule. Financial segement examine learning center income, salary, cost for every needs, income statement, internal rate of return, and payback period. Final result for this feasibility study are, learning center has 550 potential market, all technical segment for learning center compatible with goverment and standar for autismetic suffer, and learning center have 50% internal rate of return and 3,6 year payback period.